Effort-Reward Imbalance: A Risk Factor for Exposure to Workplace Bullying - Notelaers, Guy; Törnroos, Maria; Salin, Denise (Frontiers in Psychology, 2019)
Previous research shows that work environment factors are important antecedents of workplace bullying, because of the stress they may induce. While previous studies have typically used Karasek’s (1979) Job Demand Control -model and Demands Resources (Bakker & Demerouti, 2007), the present study investigates whether another important occupational stress model, that is the Effort-Reward Imbalance Model (Siegrist, 1996), is also associated to workplace bullying. A survey study in 19 Belgian organizations (n=5727) confirmed that employees experiencing an imbalance between efforts and rewards were more likely to be targets of bullying. In line with previous research, this study illustrates that stressful situations increase the risk of workplace bullying. It extends previous research by showing that also stress stemming from perceived injustice may increase employee vulnerability to bullying. More specifically, it is the first to point to a relationship between efforts-reward imbalance and bullying.